Efeitos antioxidantes do óleo essencial de Zingiber oficinale em carpa capim (Ctenopharyngodon idella) - Fortuna, Milena (2019)
Ginger (Zingiber oficinale) has several beneficial effects already investigated, in species like Wistar rats and fish (Cyprinus carpio). In the organism, the harmful effect of free radicals (ROS) occurs when they are in excessive amounts and the antioxidants combat this effect. The Grass carp (Ctenopharyngodon idella), is the one of the most important and most highly consumed freshwater fish species in the world. The aim of the present study was to investigate the effects of ginger essential oil (EOG) as an antioxidant, considering the physiology of grass carp. For this, the parameters evaluated were biochemical, blood, ion flow and acetylcholinesterase (AChE). Data are reported as mean ± SE. No mortality was registered for the duration of the experiments. Plasma glucose and protein levels did not differ significantly among the groups, as acetylcholinesterase in brain and muscle. On the three sampling times and two concentrations EOG tested, SOD activity was significantly higher in the liver (17.36 ± 3.14, 17.19 ± 3.67) and in the kidney (15.97 ± 2.42, 16.48 ± 2.95), when compared to the control group (14.63 ± 0.92, 14.09 ± 0.65), except for SOD activity in the liver after 1 hour (11.41 ± 3.42, 11.55 ± 1.58). GPx levels began to increase in the liver at 50 μL L-1 from 4 hours of treatment (23.38 ± 0.65) to 8 hours (24.63 ± 4.82) at the concentration of 100 μL L-1 , after 8 hours of exposure in the kidney (39.74 ± 7.62). The concentration of 100 μL L−1 induced the stage of light sedation, after 1 hour which lasted up to 8 hours. The ion flux of potassium (K+ ) had an influx on the concentration of 100 μL L− as the ion chloride (Cl - ) at 50 μL L-1 . The EOG induces the enzyme antioxidant activity at both concentrations, improving oxidative levels, and has a light sedation after 8 hours of expositon.